An Interdisciplinary Concept of Activity - Blunden, Andy (Outlines. Critical Practice Studies, 2009)
It is suggested that if Cultural-Historical Activity Theory (CHAT) is to fulfil its potential as an approach to cultural and historical science in general, then an interdisciplinary concept of activity is needed. Such a concept of activity would provide a common foundation for all the human sciences, underpinning concepts of, for example, state and social movement equally as, for example, learning and personality. For this is needed a clear conception of the ‘unit of analysis’ of activity, i.e., of what constitutes ‘an activity’, and a clear distinction between the unit of analysis and the substance, i.e., ultimate reality underlying all the human sciences: artifact-mediated joint activity. It is claimed that the concept of ‘project collaboration’ – the interaction between two or more persons in pursuit of a common objective – forms such a unit of activity, the single ‘molecule’ in terms of which both sociological and psychological phenomena can be theorised. It is suggested that such a clarification of the notion of activity allows us to see how individual actions and societal activities mutually constitute one another and are each construed in the light of the other.